Validation of a novel method for canine eruption assessment in unilateral cleft lip and palate patients - Khalid Alqahtani; Eman Shaheen; Sohaib Shujaat; Mostafa EzEldeen; Titiaan Dormaar; Maria Cadenas deLlano‐Pérula; Constantinus Politis; Reinhilde Jacobs (Clinical and Experimental Dental Research, 2021)
Abstract Objective The aim of this study was to propose and validate a three‐dimensional (3D) methodology for the assessment of canine eruption in patients born with unilateral cleft lip and palate (UCLP) following secondary alveolar bone graft (SABG). Methods and Materials A total of 10 patients (four females, six males; mean age: 8.8 years) with UCLP who underwent SABG were recruited. Pre‐ and 6‐month post‐operative cone‐beam computed tomography (CBCT) was acquired for all patients. Post‐operative data was registered onto pre‐operative data utilizing voxel‐based registration. Following superimposition, a segmentation process was applied to segment maxillary canine on both cleft and non‐cleft side. Thereafter, translational and rotational changes in canine position were assessed for both cleft and non‐cleft side by two observers. Results The intra‐class correlation coefficient (ICC) indicated excellent reliability (≥0.90) with inter and intra‐observer error of less than 0.05 mm. The overall ICC was found to be high for assessing both translational and rotational changes. The mean absolute inter‐ and intra‐observer difference for translational and rotational changes was found to be less than 1 mm and 3°. Conclusion The present method was found to be reliable proving to be clinically applicable for assessing maxillary canine eruption changes in both cleft and non‐cleft bone.